Santykis su atliekomis žiedinėje ekonomikoje: rūpesčio etikos perspektyva. - Bartkienė, Aistė; Bikauskaitė, Renata; Mincytė, Diana (Problems / Problemos, 2024)
This article examines the ethical dimension of waste management within the context of the circular economy. The authors argue for a shift in focus from technological and practical issues in waste management to a more holistic consideration of the ontological and ethical aspects of waste. By building on the ethics of care perspective, the article proposes a relational approach which prioritizes attentiveness, responsibility, competence, responsiveness, and involvement in addressing waste issues. By examining the five stages of care within the ethics of care framework, the study shows how ethical considerations can inform individual and collective actions within the paradigm of the circular economy. Ultimately, the article reconceptualizes waste as an integral part of our moral and ethical landscape by highlighting relationships embedded in care across private, domestic, institutional, and public domains.